TEACHING GAMES FOR UNDERSTANDING (TGfU): MEMAHAMI PENDEKATAN TAKTIK SEBAGAI MODEL PEMBELAJARAN DALAM PENDIDIKAN JASMANI - Rachman, Hari Amirullah (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2008)
For the last two decades the teaching games for understanding (TGFU) approach has caused considerable debate in games teaching. The TGFU focuses upon teaching students tactical understanding before dealing with the performance of skills, as such the TGFU offers a tactical approach to games teaching emphasizing game performance before skill performance. The aim of a tactical approach is to improve students game performance, which involves combining tactical awareness and skill execution. Tactical awareness, critical to game performance, is the ability to identify tactical problems that arises during a game and to select the appropriate responses to solve them. In tactical approach, students are placed in a game situation that emphasizes maintaining possesion before identifying and practicing passing, ball control, or support as solution to the problem. Keywords: TGFU, Tactical Approach, Game Performance